Addition of Rituximab in Reduced Intensity Conditioning Regimens for B-Cell Malignancies Does Not Influence Transplant Outcomes: EBMT Registry Analyses Following Allogeneic Stem Cell Transplantation for B-Cell Malignancies - Tomaszewska, Agnieszka (Front Immunol, 2021)
Rituximab (R) is increasingly incorporated in reduced intensity conditioning (RIC) regimens for allogeneic hematopoietic cell transplantation (alloHCT) in patients with B-cell malignancies, not only to improve disease control, but also to prevent graft-versus-host disease (GVHD). There are no randomized prospective data to validate this practice, although single center data and the CIBMTR analysis have shown promising results. We aimed at validation of these findings in a large registry study. We conducted a retrospective analysis using the EBMT registry of 3,803 adult patients with B-cell malignancies undergoing alloHCT (2001–2013) with either rituximab (R-RIC-9%) or non-rituximab (RIC-91%) reduced intensity regimens respectively. Median age and median follow up were 55 years (range 19.1–77.3) and 43.2 months (range 0.3–179.8), respectively. There was no difference in transplant outcomes (R-RIC vs RIC), including 1-year overall survival (69.9% vs 70.7%), 1-year disease-free survival (64.4% vs 62.2%), 1-year non-relapse mortality (21% vs 22%), and day-100 incidence of acute GVHD 2-4° (12% vs 12%). In summary, we found that addition of rituximab in RIC regimens for B-cell malignancies had no significant impact on major transplant outcome variables. Of note, data on chronic GVHD was not available, limiting the conclusions that can be drawn from the present study.